WORK STRESS, COPING STRATEGIES, AND EMPLOYEEDEMOGRAPHICS AS PREDICTORS OF PERCEIVED QUALITY OF LIFE AMONG FEMALE BANK EMPLOYEES - Philip Adekanmbi, Foluso; Isioma Ukpere, Wilfred (International Journal of Psychosocial Rehabilitation, 2021)
This investigation examines the influences of work stress, coping strategies, and employee demographics on the perceived quality of life among female bank employees in Nigeria’s banking industry. The sample was drawn from a selection of banks (Zenith Bank Plc, Guarantee Trust Bank Plc, Full-Range Microfinance Bank Limited, United Bank for Africa Plc, and First-City Monument Bank Plc) across Ibadan, Oyo State, Nigeria. A quantitative research approach was adopted, and questionnaires were randomly distributed. Out of 250 questionnaires, 232 were used for analysis, conducted using SPSS version 26.The findings suggest that the higher the work stress level of female bank employees, the lower their perceived quality of life, and vice versa. Additionally, coping strategies among these employees influence their perception of quality of life. The study also highlights that employee demographics, such as age, marital status, and work experience, have statistical influences on the perceived quality of life. The research confirms that work stress, coping strategies, and demographics significantly impact the perceived quality of life among female bank employees in Nigeria’s banking industry.Therefore, business leaders, management, employers, human resource managers, and recruitment agencies in Nigeria’s banks should implement psychological interventions to address work stress and coping mechanisms at all employee levels, enhancing overall quality of life and improving performance outcomes. Special attention should be given to less experienced, single, older female bank employees, as they are less likely to perceive a high quality of life in Nigeria's banking industry.